Nutrition Education for Adolescents Using Animation Videos to Increase Knowledge, Attitudes and Breakfast Behavior - Adhitya Rizky; Eti Poncorini; Suminah Suminah (Alliance oh Health Activists (AloHA), 2022)
Breakfast is beneficial for adolescents in order to maintain endurance and increase concentration in learning. About 44.60% of adolescents in Indonesia almost never have breakfast and 21.33% of them reason that there is no time for breakfast. Many factors influence knowledge about nutrition, attitudes and behavior at breakfast among adolescents, including educational factors. These factors are important to note because getting used to breakfast is one of the general messages of balanced nutrition. The purpose of this study was to analyze the effect of nutrition education using animated video media on nutritional knowledge, attitudes and breakfast behavior. This research was a quasi-experimental study with a pretest-posttest with control group design. The research was conducted in two junior high schools in Tulungagung District, East Java Province, Indonesia. This research took place in September 2022. Respondents were selected using a purposive sampling technique. The dependent variables in this study were knowledge about nutrition, breakfast attitudes and behavior; while the independent variable was nutrition education using animated videos. Data was collected using a form of knowledge about nutrition, attitudes and breakfast behavior. The collected data were analyzed using the T-test. The results showed that there were differences in the level of knowledge about nutrition, attitudes and breakfast behavior between before and after the intervention with p values of 0.001 respectively; 0.026 and 0.011. Furthermore, it can be concluded that nutrition education using animated video media is effective in increasing knowledge about nutrition, attitudes and breakfast behavior in adolescents. It is hoped that educators and health workers can use animated videos as learning media. Keywords: adolescents; animated videos; nutrition; nutritional knowledge; attitude; breakfast behavior